Direct Self‐Assembly of a 2D and 3D Star of David. (6th April 2017) - Song, Bo; Zhang, Zhe; Wang, Kun; Hsu, Chih‐Hao; Bolarinwa, Olapeju; Wang, Jing; Li, Yiming; Yin, Guang‐Qiang; Rivera, Edwin; Yang, Hai‐Bo; Liu, Changlin; Xu, Bingqian; et al.
Abstract: Two‐ and three‐dimensional metallosupramolecules shaped like a Star of David were synthesized by the self‐assembly of a tetratopic pyridyl ligand with a 180° diplatinum(II) motif and Pd II ions, respectively. In contrast to other strategies, such as template‐directed synthesis and stepwise self‐assembly, this design enables the formation of 2D and 3D structures in one step and high yield. The structures were characterized by both one‐dimensional ( 1 H, 13 C, 31 P) and two‐dimensional (COSY, NOESY, DOSY) NMR spectroscopy, ESI‐MS, ion‐mobility mass spectrometry (IM–MS), AFM, and TEM. The stabilities of the 2D and 3D structures were measured and compared by gradient tandem mass spectrometry (gMS 2 ). The high stability of the 3D Star of David was correlated to its high density of coordination sites (DOCS).